Treatment of Liver Fibrosis: A 20-Year Bibliometric and Knowledge-Map Analysis - Dai, Yun-Kai; Zhao, Zhi-Min; Liu, Chenghai (Frontiers in Pharmacology, 2022)
Objectives: To analyze the research hotspots, evolution and trends of the treatment of liver fibrosis in recent 20 years, bibliometric and knowledge-map analysis were used. Methods: Publications associated with the treatment of liver fibrosis were retrieved from Web of Science Core Collection on April 16th, 2022. CiteSpace 5.8.R3 and VOSviewer 1.6.18 were calculated to perform bibliometric and knowledge-map analysis. Results: A total of 72686 authors from 200 institutions in 134 countries/regions published 15237 papers in different academic journals. USA was the most productive country and Shanghai Jiao Tong University was the most published institution. Trauner Michael had the most published articles while Scott L. Friedman was the most frequently co-cited author. Moreover, there was frequent inter-institution cooperation between countries in the years of 2015 and after, but the before showed rare inter-institution cooperation. The journal HEPATOLOGY was both the most published publication and the most frequently co-cited one in this field. Screened keywords, such as virus-infection, inflammation, oxidative stress, activation of hepatic stellate cell (HSC), and hepatocellular apoptosis, could be both therapeutic targets and pathological mechanisms in terms of liver fibrosis. Furthermore, long-term suppression of hepatitis B virus replication and the activation of HSC were the latest hotspots and topics related to the treatment of liver fibrosis. Besides, the treatments of nonalcoholic fatty liver disease and nonalcoholic steatohepatitis were also involved in the treatment of liver fibrosis, which were both emerging topics and rapidly developing hot fields. Conclusion: This bibliometric analysis conducted a full overview of the treatment of liver fibrosis, which provided important clues and ideas for scholars focusing on this field. Not only that, the field is still in a stage of rapid development and will keep a research hotspot in the future.